Homo Ludicus: Expected Strategies and Jurisprudence - Sardo, Alessio; Esposito, Fabrizio (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2020)
Joint intentionality is a concept en vogue in general jurisprudence. Richard Ekins has relied on joint intentionality to account for how legislatures can have intentions. At a more foundational level, Scott Shapiro has relied on shared intentions for explaining the normativity of legality. In this essay, we propose a metaphysically parsimonious approach called “expected-strategies approach”, combined with a teamreasoning approach to legislation. Based on a game-theoretic perspective, this approach anchors normativity to our capacity of coordinating our actions, both at the level of the law-maker, and at the level of the legal subjects. We show that for this coordinating function, an understanding of other players’ expected strategies is sufficient. The expected-strategies approach portrays the rational agent as a homo ludicus, whose key social virtues are stability and predictability. Keywords: Joint Intention; Legislative Intention; Game Theory; Legal Normativity; Expected-Strategy Approach Index: 1. Grounding Normativity in Equilibria – 2. Richard Ekins: Lawmaking and Joint Intentions – 3. Team Reasoning – 4. Scott Shapiro’s Planning Theory of Law – 5. A Different Solution to The Possibility Puzzle: The Normativity of Legality Derives from Expectations – 6. The Expected-Strategy Approach – 7. Conclusions: Homo Ludicus – A Predictable Fellow – References